Berlin Workshop Series 2008 : Agriculture and Development - Kochendörfer-Lucius, Gudrun; Pleskovic, Boris (Washington, DC : World Bank, 2012)
The workshop brings diverse perspectives from outside the World Bank, providing a forum in which to exchange ideas and debate in the course of developing the World Development Report (WDR). Participants at the 2006 Berlin Workshop gathered to discuss challenges and successes pertaining to agriculture and development. Agriculture is the major sector contributing to economic development in many poor countries. Three out of every four poor people in developing countries live in rural areas. As globalization accelerates, development policies should tackle future challenges in agriculture arising from the scarcity of natural resources and globalization. The author highlights the paramount importance of redefining the framework for agriculture, providing us with food for thought and putting forward suggestions that need greater reflection and more detailed discussion. The contribution focuses on three main topics. First, the author presents some considerations on global agricultural development and trade. The author describes the different approaches to agricultural development, outcomes and effects of these approaches and evaluates which nations or which population groups are benefiting, as this could help to develop target group oriented strategies in poverty alleviation and agriculture. Second, the author takes a critical look at how agriculture and the rural sector can be an effective engine for growth. Another issue on the agenda is to determine what agriculture needs in the way of technology, infrastructure, and financial support to become a growth engine? These new insights should contribute to an appropriate formulation and implementation of tailored agriculture for development programs. Finally, the author looks at development in connection with systematic capacity building and training, pointing out the need to define sound capacity-building measures in terms of agriculture as well as to determine how these could be used more effectively.